Technology Acceptance and Planned Behavior: How TikTok Impacts Digital Entrepreneurship Intention among University Students in Batam City - Cindy Juliandry; Indasari Deu; Eryc (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
TikTok application is changing the shape of the economy and how young people see it as an opportunity. This study investigates the impact of TikTok application on digital entrepreneurship intentions among university students in Batam City. Leveraging the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB), the research explores how perceived usefulness, perceived ease of use, attitudes, subjective norms, and perceived behavioral control influence students' entrepreneurial aspirations. A quantitative method with purposive sampling was used, targeting 460 respondents. The findings reveal that TikTok's user-friendly features and algorithmic design significantly affect digital entrepreneurship intentions, facilitating accessibility and fostering innovative business practices. The results underscore the importance of integrating digital tools into entrepreneurship, providing practical insights for educators, platform developers, and young people to enhance entrepreneurial engagement in the digital economy. Despite geographical limitations, this study contributes to the theoretical understanding of technology-driven entrepreneurship and highlights areas for future exploration.